The potential beneficial effects of ethyl pyruvate on diabetic nephropathy: an experimental and ultrastructural study - Mehmet Veysi Bahadir; Yasar Yildirim; Ozlem Pamukcu Baran; Sait Polat; Hasan Akkoc; Selcuk Tunik (Polish Journal of Pathology, 2016)
Oxidative stress is one of the main causes of diabetic nephropathy, which is a complication of diabetes mellitus (DM). The aim of this study was to investigate the possible role of ethyl pyruvate (EP) in streptozotocin-induced diabetic rats’ kidney. Four groups (n = 8) of male Wistar albino rats were used as follows: control group rats received only sodium citrate buffer solution intraperitoneally (ip). The EP group was given 50 mg/kg EP ip. In the DM group, diabetes was induced by streptozotocin. The DM + EP group received 50 mg/kg EP ip. All animals received daily treatment for 14 days, and at the end of the study the kidneys were removed: the left kidney of the rats was used for malondialdehyde (MDA) analysis and the right kidney for histological examination. There was normal appearance of the kidney tissues in the control and the EP-administered groups. In the DM group, there was evident basement membrane thickening and enlargement of mesangial matrix; swelling in some tubular epithelial cells was also noticeable. In the DM+EP administered group, nearly the same appearance as the control group and relative thickening in the glomerular basal membrane were observed. The antioxidant effect of ethyl pyruvate improved the renal structures in the DM + EP group.